IMPROVING PRODUCT QUALITY AND PROFITABILITY THROUGH PROCESS STANDARDIZATION IN A CHOCOLATE MANUFACTURING SME - Pardave Vasquez, Yoshua Emilio; Burga Hernandez, Yadira Cinthia; Sotomayor Burga, Juan Luis; Diaz Diaz, Marco Antonio (LACCEI, 2025)
Ensuring production quality is critical to the sustainability and profitability of small-scale manufacturing enterprises. Within the chocolate industry, the presence of defective products undermines both operational efficiency and market competitiveness. Despite this, many companies still operate without standardized procedures to mitigate errors and control production costs, resulting in economic losses and compromised quality. This study evaluates the impact of designing and implementing a Procedures Manual on the reduction of product defects in a chocolate manufacturing company. A non-experimental, quantitative research design was employed, analyzing cost indicators before and after the intervention. The findings revealed a substantial decrease in defective outputs, yielding a total economic gain of US 6,401.83, an Internal Rate of Return (IRR) of 68%, a Net Present Value (NPV) of US 4,736.83, and a Benefit-Cost ratio of 3.84. These results underscore the importance of standardization in small-scale manufacturing environments, highlighting how procedural implementation can significantly enhance production efficiency, profitability, and market competitiveness.